Robo2 Receptor Gates the Anatomical Divergence of Neurons Derived From a Common Precursor Origin - Wurmser, Maud; Muppavarapu, Mridula; Tait, Christine Mary; Laumonnerie, Christophe; González-Castrillón, Luz María; Wilson, Sara Ivy (Frontiers in Cell and Developmental Biology, 2021)
Sensory information relayed to the brain is dependent on complex, yet precise spatial organization of neurons. This anatomical complexity is generated during development from a surprisingly small number of neural stem cell domains. This raises the question of how neurons derived from a common precursor domain respond uniquely to their environment to elaborate correct spatial organization and connectivity. We addressed this question by exploiting genetically labeled mouse embryonic dorsal interneuron 1 (dI1) neurons that are derived from a common precursor domain and give rise to spinal projection neurons with distinct organization of cell bodies with axons projecting either commissurally (dI1c) or ipsilaterally (dI1i). In this study, we examined how the guidance receptor, Robo2, which is a canonical Robo receptor, influenced dI1 guidance during embryonic development. Robo2 was enriched in embryonic dI1i neurons and loss of Robo2 resulted in misguidance of dI1i axons, whereas dI1c axons remained unperturbed within the mantle zone and ventral commissure. Further, Robo2 profoundly influenced dI1 cell body migration, a feature that was partly dependent on Slit2 signaling. These data suggest that dI1 neurons are dependent on Robo2 for their organization. This work integrated with the field support a model whereby canonical Robo2 versus non-canonical Robo3 receptor expression facilitates projection neurons derived from a common precursor domain to read out the tissue environment uniquely giving rise to correct anatomical organization.